(untitled) (International Journal of Engineering and Computer Science, 2018)
Secret sharing has drawn much attention in the research community, Secret sharing refers to methods for distributing a secret amongst a group of participants, each of whom is allocated a share of the secret. The secret can be reconstructed only when a sufficient number, of possibly different types, of shares are combined together, individual shares are of no use on their own. Message divides into n pieces and called shares or shadows, any t(threshold value) of them can be used to reconstruct the message. A threshold value is set based on the required number of context conditions for permitting data access, if a threshold number of context parameters are satisfied then the decryption key is generated from the corresponding key shares and the data is decrypted. Secret sharing schemes are ideal for storing information that is highly sensitive and highly important.